The Value of Reference Letters - Abel, Martin; Burger, Rulof; Piraino, Patrizio (World Bank, Washington, DC, 2017)
This paper shows that reference letters from former employers alleviate information asymmetries about workers' skills and improve both match quality and equity in the labor market. A resume audit study finds that using a reference letter in the application increases callbacks by more than 60 percent, with women driving the effect. Letters are effective because they provide valuable information about workers' skills that employers use to select applicants of higher ability. A second experiment, which encourages job seekers to obtain and use a reference letter, finds consistent results. In particular, employment rates for women encouraged to obtain a letter increase by 49 percent, closing the gender gap in the sample.